Barriers to care for adolescents with borderline personality disorder. (February 2021) - Wall, Kiana; Kerr, Sophie; Sharp, Carla
Highlights: Early intervention for adolescents with personality pathology is of critical importance. However, there are barriers to obtaining mental health care for adolescents with personality pathology. Barriers result from interaction between patient and system characteristics at each juncture of the access to care pathway. Recommendations for addressing barriers to care, thereby increasing access, are provided. Abstract : Intervention for borderline personality disorder (BPD) in adolescence is crucial as early onset of the disorder predicts more severe course, and intervention 'late' in the course of the disorder is associated with more negative outcomes. In spite of this, access to services is poor. This is because several unique barriers to accessing care exist for adolescents with BPD. In this article we highlight key barriers to care for adolescents with BPD utilizing a conceptual model for understanding health care access that emphasizes the interaction between patient and health care system characteristics. We conclude with proposed recommendations to address these identified barriers.